Potential mechanisms for a role of metabolic stress in hypertrophic adaptations to resistance training - Schoenfeld, B. J. (Sports Medicine, 2013)
It is well established that regimented resistance training can promote increases in muscle hypertrophy. The prevailing body of research indicates that mechanical stress is the primary impetus for this adaptive response and studies show that mechanical stress alone can initiate anabolic signalling. Given the dominant role of mechanical stress in muscle growth, the question arises as to whether other factors may enhance the post-exercise hypertrophic response. Several researchers have proposed that exercise-induced metabolic stress may in fact confer such an anabolic effect and some have even suggested that metabolite accumulation may be more important than high force development in optimizing muscle growth. Metabolic stress pursuant to traditional resistance training manifests as a result of exercise that relies on anaerobic glycolysis for adenosine triphosphate production. This, in turn, causes the subsequent accumulation of metabolites, particularly lactate and H+. Acute muscle hypoxia associated with such training methods may further heighten metabolic buildup. Therefore, the purpose of this paper will be to review the emerging body of research suggesting a role for exercise-induced metabolic stress in maximizing muscle development and present insights as to the potential mechanisms by which these hypertrophic adaptations may occur. These mechanisms include increased fibre recruitment, elevated systemic hormonal production, alterations in local myokines, heightened production of reactive oxygen species and cell swelling. Recommendations are provided for potential areas of future research on the subject.